2017
DOI: 10.3390/app7080774
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Field Analysis of an Electric Dipole Antenna Based on a Surface Integral Equation in Multilayered Dissipative Media

Abstract: Abstract:In this paper, a novel method based on the Poggio-Miller-Chang-Harrington-Wu-Tsai (PMCHWT) integral equation is presented to study the electromagnetic fields excited by vertical or horizontal electric dipoles in the presence of a layered region which consists of K-layered dissipative media and the air above. To transform the continuous integral equation into a block tridiagonal matrix with the feature of convenient solution, the Rao-Wilton-Glisson (RWG) functions are introduced as expansion and testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, irrigating tomato by 100% fresh water had the highest values, while using of 100% agricultural drainage water displayed the lowest values. Also, Xu et al (2017) and studied the role of magnetic treatment of saline water on seed germination of potato and corn crop. Their results showed that seedling germination rate is considerably increased with the use of magnetic-treated saline water (EC = 4 ds m -1 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, irrigating tomato by 100% fresh water had the highest values, while using of 100% agricultural drainage water displayed the lowest values. Also, Xu et al (2017) and studied the role of magnetic treatment of saline water on seed germination of potato and corn crop. Their results showed that seedling germination rate is considerably increased with the use of magnetic-treated saline water (EC = 4 ds m -1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to use a volume based method to study the interaction between dipoles and objects, such as the finite element method (FEM), special attention is needed to handle the mesh in the domain around a dipole and how the mesh evolves to the surrounding space [15]. Concerning surface based methods, the most popular one is the method of moments (MoM) [16] which was traditionally used to calculate the electromagnetic field of an electric dipole antenna for applications in Through-the-Earth communication. MoM can calculate the far field, but in spite of its popularity, performs much less accurate when accessing the near field or the surface field due to the congenital hypersingularies of this method.…”
mentioning
confidence: 99%